Identification of proteolytic bacteria from thai traditional fermented foods and their allergenic reducing potentials - P. Phromraksa (2018)
This study aimed to identify proteolytic bacteria from Thai traditional fermented foods and investigate their allergenic reducing potentials to wheat and milk allergens. Nine bacteria were isolated from fermented foods as follows: fermented soybean seeds (Thua Nao), fermented soybean paste (Thua Nao), wheat flour dough of steamed stuffed bun (Sa La Pao), and soaked rice from Thai fermented rice-noodle (Kha Nhom Jeen) processing. Both phenotypic and genotypic identifications were used in this study. It was found that all isolates were Gram-positive rods. Seven isolates were matched and identified as Bacillus subtilis by both techniques, and the remaining 2 isolates were phenotypically and genotypically identified as B. licheniformis and B. subtilis, respectively. The concentrated crude enzyme of B. subtilis DB and SR could reduce allergenicity of gliadin by hydrolyzing the allergenic gliadin fragments detected by immunoblotting. Furthermore, the enzyme of B. subtilis DB could also reduce allergenicity of β-lactoglobulin (β-LG) detected by hydrolyzing the major allergenic epitope of β-LG at Gln35- Ser36position. B. subtilis DB and SR can be applied for the production of hypoallergenic wheat flour or milk food products. © 2008 Institute of Food Technologists.